The effect of discretization on the accuracy of two district heating network models based on finite-difference methods. (September 2018) - Vivian, J.; de Uribarri, P. Monsalvete Álvarez; Eicker, U.; Zarrella, A.
Abstract: District heating and cooling (DHC) networks play a fundamental role in the transition towards a sustainable supply of heating and cooling, due to their ability to integrate any available source of thermal energy and to distribute it to the buildings. However, the use of renewable non-constant sources together with the variable heat demand of the buildings creates instable and pronounced transient operating conditions. In order to analyse the hydraulic and thermal behaviour and the dynamics occurring within these networks, several physical models based on different methods were proposed by previous researchers. Numerical thermal models based on finite difference methods (FDM) were pointed out to suffer from artificial diffusion when simulating the propagation of heat through the network. However, due to a wide and well-known literature on these methods, they are still used by many researchers and are therefore worth being investigated. The present paper analyses the effects of artificial diffusion using two models based on two different first-order approximation schemes. An ideal temperature wave and a dataset from a real DH network were used to evaluate the accuracy of the models using different discretization levels in time and space. As a result, the paper provides a framework to set a proper discretization when simulating a DHC network with FDM-based models considering both the expected accuracy and the computation time as criteria.